Science projects about chemistry - Gardner, Robert, 1929-; Delisle, Stephen F. (Berkeley Heights, N.J. : Enslow, 1994)
Presents ideas for science projects about chemistry.
Matter : it has properties of its own -- Solutions : making things disappear -- Analysis : separating and identifying substances -- Chemical reactions : when new substances form -- Acid + base : a colorful chemical reaction -- Oxidation : reactions with oxygen.
"updated with internet sites"--Cover.
Includes bibliographical references (p. 120-121) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Chemistry -- Experiments -- Juvenile literature; Science projects -- Juvenile literature; Science -- Exhibitions -- Juvenile literature; Chemistry -- Experiments; Experiments; Science projects; Chemistry -- Experiments; Science projects; Science -- Experiments